Agriculture performance of table cassava cultivars in west region of Pará - Bizerra Barros, Ianna; Maia de Sousa, Arlem Dalvany; Alves de Sousa, Mateus; Camacho Palomino, Edwin (Scientia Agraria Paranaensis, 2021)
The cassava crops have a great diversity of cultivars, mostly creole, being necessary studies that aim the selection of materials able to express its productive potencial in distinctive areas of Brazil. Thus, this work aimed to assess the agronomic characteristics and the productive of seven cultivars of table cassava, in the West region of Pará. The experiment was carried out in a rural property, in the municipality of Mojuí dos Campos (Pará). The experimental design was randomized blocks, with three repetitions. The treatments were constituted of local cassava cultivars (Água Morna, Roxa do Curudi, Amarelona, Olhinho, Máximo, Tabocal II e Paço Branco). The evaluated characteristics were: height of plants – HP (m), height of the first ramification – HR (m), diameter of the plant stem – DPS (cm), number of sprouts - NS, number of harvested roots - NHR, root fresh biomass – RFB (g), root dry biomass – RDB (g), diameter of roots –DR (cm), length of roots – LR (cm) and productivity (PR). For the characters in the aerial part, the ‘Roxa do Curundi’ cultivar showed the highest HP and HR ‘Máximo e Paço Branco’ expressed the highest DPS and NS, respectively. The cassava cultivars studied distinguished as to the characteristics of agronomic interest for inclusion in plant breeding programs of the species in the western region of the state of Pará. Among the evaluated cultivars, ‘Paço Branco’ is recommended for agricultural improvement, as it presents desirable characteristics, such as higher productivity and smaller size.